The Division of Marital Joint Property: Legal Framework and Gender Implications in North Macedonia - Metaj-Stojanova Albana (SEEU Review)
This paper explores the legal framework governing the division of joint ownership in marital property in North Macedonia, with a particular focus on gender implications. It critically analyzes the Family Law Act and the Law on Ownership and Other Real Rights to assess how these provisions function during marriage dissolution due to divorce or death. By employing a qualitative, legal-analytical approach, the research assesses legislative texts and relevant case law to explore the extent to which current laws ensure equitable property division, irrespective of gender or economic contribution. In addition to legal analysis, the research utilizes case law to highlight and illustrate discrepancies between the law’s theoretical principle of equal division and its real-world application, particularly where traditional gender roles are concerned. It discusses how traditional expectations around women’s unpaid contributions, such as caregiving and household management, often result in outcomes that disadvantage women. Women, especially those who have forgone paid employment to fulfill domestic roles, face significant challenges in securing an equal share of marital property.